ANALISIS EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL PERKREDITAN PADA PT. BANK PEMBANGUNAN DAERAH PAPUA CABANG MANADO - Krar, Sonaria; Tinangon, Jantje J.; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
Â AÂ goodÂ AccountingÂ Â InformationÂ Â SystemÂ canÂ help Â companyÂ toÂ provideÂ theÂ companyâsÂ needÂ forÂ Â otherÂ informationÂ relatedÂ Â toÂ busynessÂ processÂ thatÂ existÂ withinÂ theÂ company. ThisÂ researchÂ studyÂ atÂ PT. RegionalÂ bankÂ developmentÂ papuaÂ branchÂ manado.ThisÂ studyÂ Â aimsÂ toÂ Â knowÂ effectivenessÂ ofÂ Â Â information accountingÂ systemÂ andÂ internalÂ controlÂ ofÂ kreditÂ onÂ PT.regionalÂ Â bankÂ developmentÂ papuaÂ branchÂ manado.ThisÂ studyÂ used a deskriptiveÂ qualitativeÂ methodÂ isÂ aÂ methodÂ thatÂ isÂ doneÂ byÂ classifyingÂ dataÂ and Â Â inormationÂ whichÂ isÂ obtainedÂ byÂ variousÂ technicquesÂ suchÂ asÂ survey, interviews,Â andÂ others. SoÂ getÂ aÂ relevantÂ conclusion.The resultsÂ ofÂ Â theÂ Â analysisÂ Â ofÂ theÂ conclusionÂ thatÂ theÂ informationÂ systemÂ Â andÂ Â internalÂ controlÂ ofÂ PT. bankÂ PapuaÂ manadoÂ branchÂ hasÂ beenÂ Â runningÂ well, andÂ inÂ accordanceÂ withÂ proceduresÂ thatÂ haveÂ beenÂ setÂ byÂ theÂ bankÂ indonesian.Â AllreadyÂ meetÂ theÂ characteristicsÂ andÂ Â elementsÂ Â ofÂ Â internalÂ control.Keywords : InformationÂ AccountingÂ System,Â InternalÂ control,Â Credit.